2012
DOI: 10.1186/1477-7819-10-265
|View full text |Cite
|
Sign up to set email alerts
|

Sleeve lobectomy versus pneumonectomy for non-small cell lung cancer: a meta-analysis

Abstract: AimIt is controversial that whether sleeve lobectomy (SL) should be promoted more worthy than pneumonectomy (PN) in suitable patients.MethodsWe searched all studies that had been published in English from PUBMED and Embase which compared the short-term and long-term outcomes of SL and pneumonectomy (PN) in patients with non-small cell lung cancer (NSCLC).ResultsNineteen studies met our criteria with a combined total of 3878 subjects, of which 1316 (33.9%) underwent SL and 2562 (66.1%) underwent PN. The odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
3
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 23 publications
1
37
3
8
Order By: Relevance
“…In order to retain greater respiratory function, when the tumor only invades the intermediate bronchus without invading the middle lobe bronchus and parenchyma, the surgeon can choose sleeve resection to retain the middle lobe . However, more than a quarter of patients in this study with LN metastasis, especially those with N2 LN metastasis, had metastatic tumor cells left in the middle lobe, thus radical resection cannot be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In order to retain greater respiratory function, when the tumor only invades the intermediate bronchus without invading the middle lobe bronchus and parenchyma, the surgeon can choose sleeve resection to retain the middle lobe . However, more than a quarter of patients in this study with LN metastasis, especially those with N2 LN metastasis, had metastatic tumor cells left in the middle lobe, thus radical resection cannot be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…For central lung cancer patients, SR is preferred by thoracic surgeons for preserving lung function, better postoperative life quality and survival . A recent meta‐analysis also showed that SR was more suitable for lower rates of mortality and better prognoses. Unlike these reports, Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…Die 30-Tage-Mortalität nach Pneumonektomie liegt je nach Literatur bei 6-13,3%, im Gegensatz zur Lobektomie bei nichtkleinzelligem Bronchialkarzinom mit 2,9-4% [21,25]. Im Vergleich zu anderen Organresektionen in der Tumoronkologie, beispielsweise der Gastrektomie oder der Operation nach Whipple mit einer perioperativen Mortalität von <5%, weist die Pneumonektomie eine hohe perioperative Mortalität auf.…”
Section: Folgen In Der Frühphaseunclassified
“…Aufgrund der höheren Lebensqualität sowie des besseren Langzeitüberlebens der Patienten nach Manschettenlobektomie sollten, falls onkologisch vertretbar, parenchymsparende Eingriffe der Pneumonektomie vorgezogen werden [12,25]. Um dieses Ziel zu erreichen, sollten gegebenenfalls neoadjuvante multimodale Verfahrenskonzepte zum Downstaging angewandt werden.…”
Section: Lebensqualität Nach Pneumonektomieunclassified